Chemical and Microbiology Analysis of Salted Anchovies (Stolephorus sp.) in East Denpasar Traditional Market - DellaXâ€™ma Nandari; Anak Agung Made Semariyani; Ni Made Ayu Suardani Singapurwa (Warmadewa University Press, 2020)
Jengki anchovies are one of the raw food ingredients that are preserved using salt. Basically, salting is done to reduce the water content in the fish so that bacteria cannot live and develop. This study aims to determine the chemical and microbiological contamination of salted anchovies in East Denpasar Traditional Market. This research is a descriptive study using survey and experimental methods in the laboratory. Based on data from the Department of Industry and Trade in Denpasar, there are 7 traditional markets in East Denpasar. The number of samples studied was 43 samples from 75 existing populations. The parameters of this research were formaldehyde, moisture content, TPC, E. coli and organoleptics. The results showed that none of the 43 samples contained formalin. The results of the water content test were obtained that all samples met the SNI 8273: 2016 requirements. From the results of the TPC test, 35 samples met the requirements and 8 samples exceeded the limits set by SNI 8273: 2016, namely the maximum limit of TPC contamination, namely 1.0 Ã— 105 colonies / gram. The E. coli test results from 43 samples met the SNI 8273: 2016 requirements, namely the maximum limit of E. coli contamination Ë‚3.6 APM / gram. From the results of the organoleptic test on appearance, smell, taste, texture, fungus and overall acceptance, all assessments were significantly different, with the characteristics of a dull to clean bright appearance, specific to type, specific odor but less strong, salty taste and less specific type, dry solid texture to dense less dry.